(untitled) (Journal of Hama University, 2026)
The research aims to identify teachers’ attitudes toward education in virtual schools during the basic education stage in some Syrian cities. The researcher adopted an analytical descriptive approach, and the research tool consisted of an 18-item questionnaire. The questionnaire was administered to a sample of 180 male and female teachers in virtual schools across several Syrian cities (Hama, Homs, Aleppo, Deir ez-Zor, As-Suwayda, Latakia, and Tartus). The findings revealed statistically significant differences in teachers’ attitudes toward education in virtual schools, favoring the sample mean. Thus, teachers’ attitudes toward education in virtual schools during the basic education stage in some Syrian cities are above average. Additionally, there were no statistically significant differences in teachers’ attitudes based on variables such as academic qualifications, years of experience in virtual schools, or participation in training courses. The researcher recommended enhancing digital training for teachers in virtual schools to create an engaging and enjoyable learning environment for students, as well as developing interactive platforms in virtual schools using games and augmented reality.